STRENGTHENING SOCIAL SCIENCE LEARNING THROUGH INTEGRATION OF GLOBAL GENDER EQUALITY PERSPECTIVES - jumriani; Deasy Arisanty; Ersis Warmansyah Abbas; Mutiani; Sarbaini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Gender equality is a global issue that continues to face challenges in its implementation across countries. School learning plays a strategic role in instilling the values of justice and equality from an early age. One such approach is through the subject of Social Studies. This article aims to examine how strengthening Social Studies learning through the integration of a global perspective on gender equality makes learning more relevant, contextual, and better able to foster critical awareness in students. This research uses a literature review. Data were obtained from various literature sources, including national and international journal articles and books related to Social Studies learning themes, gender equality, and global perspectives. Data analysis was conducted descriptively and analytically by mapping the relationship between ten main Social Studies themes and gender equality issues in a global context. The results of the study indicate that gender equality can be integrated comprehensively into Social Studies subject themes, such as culture, history, environment, individual identity, social relations, power, economics, technology, global connections, and citizenship. The integration of a global perspective into Social Studies learning helps students understand gender equality as a cross-border, cross-cultural social issue. Thus, Social Studies learning plays a vital role in fostering inclusive, just, and responsible attitudes among global citizens.